Effect of the degree of follicular diameter ≥18mm differentiation on the day of hCG administration to the outcome of controlled ovarian hyperstimulation (COH) - Xu, Hongyi; Chen, Qi; Tian, Jiarong; Chen, Xin; Zhang, Xin; Li, Xin; Wu, Ying; Zhang, Changjun; Zhang, Ying (Frontiers in Endocrinology, 2024)
Objective: To explore the impact of the level of differentiation in a minimum of two follicles with a diameter of ≥18 mm on the outcome of controlled ovarian hyperstimulation on the day of human chorionic gonadotropin (hCG) administration. Methods: Single-center data from January 2018 to December 2021 was retrospectively analyzed for 1,199 patients with fresh embryo transfer for assisted reproduction. The absolute value of the standard deviation of the follicle size of at least 2 follicles ≥18 mm in diameter in both ovaries on the day of hCG was taken as the degree of differentiation of the dominant follicle after ovulation induction, based on the standard deviation response to the degree of dispersion of the data. The degree of follicular differentiation was divided into 3 groups according to the size of the value, and the general clinical conditions, laboratory indexes, and clinical outcomes of the patients in the 3 groups were compared. Results: Among the three groups, the body mass index (BMI) of the ≤1s group was lower than that of the other two groups (P < 0.05), while the follicle-stimulating hormone (FSH) and Anti-Mullerian hormone (AMH) were higher (P < 0.05), and the implantation rate and clinical pregnancy rate were significantly higher than those of the other two groups (P < 0.01). After multifactorial logistic regression to correct for confounding factors, with the ≤1s group as the reference, the implantation rate, hCG-positive rate, clinical pregnancy rate and live birth rate of embryo transfer in the ≥2S group were significantly lower (P < 0.01). The results of curve fitting analysis showed that the live birth rate decreased gradually with the increase of the absolute standard deviation (P=0.0079). Conclusion: Differences in follicle diameters ≥18 mm on the day of hCG injection did not have an impact on embryo quality, but had an impact on pregnancy outcomes. The less the variation in follicle size, the more homogeneous the follicle development and the higher the likelihood of live births.